Variations in the Inferred Cosmic-Ray Spectral Index as Measured by Neutron Monitors in Antarctica - Pradiphat Muangha; David Ruffolo; Alejandro Saiz; Chanoknan Banglieng; Paul Evenson; Surujhdeo Seunarine; Suyeon Oh; Jongil Jung; Marcus Duldig; John E Humble (2024)
A technique has recently been developed for tracking short-term spectral variations in Galactic cosmic rays (GCRs) using data from a single neutron monitor (NM), by collecting histograms of the time delay between successive neutron counts and extracting the leader fraction L as a proxy of the spectral index. Here we analyze L from four Antarctic NMs from 2015 March to 2023 September. We have calibrated L from the South Pole NM with respect to a daily spectral index determined from published data of GCR proton fluxes during 2015-2019 from the Alpha Magnetic Spectrometer (AMS-02) on board the International Space Station. Our results demonstrate a robust correlation between the leader fraction and the spectral index fit over the rigidity range 2.97-16.6 GV for AMS-02 data, with uncertainty of 0.018 in the daily spectral index as inferred from L. In addition to the 11 yr solar activity cycle, a wavelet analysis confirms a 27 day periodicity in the GCR flux and spectral index corresponding to solar rotation, especially near sunspot minimum, while the flux occasionally exhibits a strong harmonic at 13.5 days. The magnetic field component along a nominal Parker spiral (i.e., the magnetic sector structure) is a strong determinant of such spectral and flux variations, with the solar wind speed exerting an additional, nearly rigidity-independent influence on flux variations. Our investigation affirms the capability of ground-based NM stations to accurately and continuously monitor cosmic-ray spectral variations over the long-term future.